Bioethical analysis of face transplantation in Brazil - Katia Torres Batista; Eliane Maria Fleury Seidl (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: This update on bioethical aspects of face transplantation reviews the literature on the current status of organ and face transplantation, the significance of the human face, and the human face as a vital organ. METHODS: This was a narrative bibliographic review, with documentary analysis of face transplantation in the last 10 years. RESULTS: A search of the PubMed database identified 8,259 papers with the keyword face transplantation, 28 articles with the keywords face transplantation and bioethics, and 4,877 papers with the keyword organ transplant ethics; documents related to legislation were found in the Brazilian Association of Organ Transplantation (Associação Brasileira de Transplantes de Órgãos - ABTO). CONCLUSION: The experience of countries where face transplantation has been performed has shown that this is a viable option for the reconstruction of severe facial lesions. However, face transplantation is considered an experimental procedure with high risk of complications and costs, and requires a multidisciplinary team and the lifetime use of immunosuppressants. To date, this procedure is only indicated for a small group of patients. From a bioethics standpoint, it should be noted that, despite providing consent, the level of risk acceptable to the recipient must be assessed. Who will be responsible for the costs related to the procedure? When can public resources be used to justify individual rights over public rights?